Penghulu-penghulu keraton bidang agama, hukum, dan pendidikan di Kasunanan dan Mangkunegaran tahun 1936-1947 - Purbaningrum, Fariska Dwi; Kusairi, Latif (Historiography: Journal of Indonesian History and Education, 2023)
This study aims to analyze the role of the penghulu both of the Keraton Kasunanan and Kadipaten Mangkunegaran in the late 19th and early 20th centuries. Especially, the political and cultural backround of the Surakarta Penghulu Conference was held in 1936 which took place at the Mangkunegran pavilion. The method of the research uses historical methodology, consists of heuristics, verification, interpretation and historiography. Various sources in the form of archives, newspapers, magazines, books, journals, articles, and the web used in this research. The results of this study explain the early history of the formation of the princes of the Kasunanan palace and the Managkunegaran palace, the prince of the palace is a position that has been inherited by the Demak kingdom for the following Islamic kingdoms, namely Mataram, Pajang, Kasunanan to Mangkunegaran. The bureaucratic structure is still maintained with the existence of the abdi daelm penghulu in it. The penghulu carries out his duties assisted by several staff including modin, kayim, muezzin, chief khakim, khatib, etc. The prince has duties in various fields, namely in the religious field which includes preaching, management of the Great Mosque, in the legal field of the prince becoming qodi to settle NTCR cases (Marriage, Divorce, Divorce and Reconciliation), as well as resolving marital disputes, in the field of education for the prince to establish schools. Penghulu also holds a meeting every year to discuss programs that are advancing.  Penelitian bertujuan untuk menganalisis peran penghulu Keraton Kasunanan dan Kadipaten Mangkunegaran yang pada abad akhir ke-19 dan awal abad ke-20 bagi agama Islam di wilayah kekuasaannya. Penelitian ini juga bertujuan membahas latar belakang dilakukannya konferensi penghulu Surakarta pada tahun 1936 yang bertempat di pendopo Mangkunegran. Penelitian ini menggunakan metode sejarah, terdiri dari 4 tahapan penelitian: heuristik, kritik, interpretasi dan historiografi. Berbagai sumber yang digunakan berupa arsip, koran, majalah, buku, jurnal, artikel, dan web yang terkait dengan penelitian ini. Hasil dari penelitian ini menjelaskan tentang sejarah awal terbentuknya penghulu keraton Kasunanan dan keraton Managkunegaran, penghulu keraton merupakan jabatan yang telah diwariskan oleh kerajaan demak untuk kerajaan Islam berikutnya yaitu Mataram, Pajang, Kasunanan sampai dengan Mangkunegaran. Struktus birokrasi masih dipertahankan dengan adanya abdi daelm penghulu di dalamnya. Penghulu menjalankan tugas dibantu oleh beberapa staf diantaranya ada modin, kayim, muadzin, penghulu khakim, khatib, dll. Penghulu bertugas dalam berbagai bidang yaitu di bidang keagamaan yang meliputi dakwah, kepengurusan masjid Agung, dalam bidang hukum penghulu menjadi qodi untuk menyelesaikan perkara NTCR (Nikah, Talak, Cerai dan Rujuk), serta menyelesaikan persengketaan mawaris, bidang pendidikan para penghulu mendirikan sekolahan. Penghulu juga mengadakan pertemuan pada setiap tahunya dengan membahas program-program yang bersifat memajukan.